Inside out an insider's account of Wall Street - Levine, Dennis B.; Hoffer, William (Putnam, 1991)
Paperback copies have subtitle: A true story of greed, scandal, and redemption.
Keywords: Levine, Dennis <1952->; Insider trading in securities -- United States; Investment banking -- Corrupt practices -- United States; USA